Analysis of Factors Causing Variation Orders and their Impact on Construction Contract Value of Main Dam Projects - Siahaan, Hasiholan Christian; Wiguna, I Putu Artama (Universitas Ibn Khaldun Bogor, 2024)
The Indonesian government has been actively engaged in extensive dam construction initiatives aimed at harnessing water resources for diverse purposes such as agricultural irrigation, clean water supply, flood control, power generation, and tourism. However, the construction of each main dam project faces challenges, particularly in the form of variation orders that lead to increases in construction costs. This research investigated the factors contributing to variation orders in main dam projects in Indonesia and to assess their impact on the overall construction costs. A comprehensive literature review was performed to identify variation order factors previously studied by researchers. Subsequently, secondary data were gathered through questionnaires administered to various stakeholders involved in main dam projects, including contractors, consultants, and owners. The analysis of questionnaire responses revealed a total of 26 indicators contributing to variation orders, which were categorized into 9 consultant-related factor, 8 owner-related factor, 6 external factor, and 3 contractor-related factor. Four indicators, including the alignment of tender drawings and field conditions, natural changes (weather/geology), changes in work items, and the complexity of dam design, were identified as having mean values greater than 4 on a 5-point Likert scale. This indicates strong consensus among respondents that these indicators significantly contribute to variation orders. A subsequent questionnaire aimed to evaluate the impact of these 26 variation order indicators on construction cost increases. The collected data from respondents was analyzed using multiple linear regression. The results revealed that the contractor-related factor had the most substantial impact on cost increases with a coefficient of 0.14, followed by the external factor at 0.067, and the owner-related factor at 0.04.